THE USE OF POWERPOINT AS THE INSTRUCTIONAL MEDIA IN TEACHING ENGLISH FOR YOUNG LEARNERS - Triana Dewi; Evie Kareviati (IKIP Siliwangi, 2021)
This research is about the use of powerpoint as the instructional media in teaching english for young learners at the first semester of the sixth grade students of SDN Baros Mandiri 5. The objective of this research are to analyze the use of powerpoint as the instructional media in teaching english for young learners. Data is collected through observation and interview. The reseacher chose class VIB as sample which consisted of 30 students. The data is then analyzed using observation sheets. The observations is began at 08.30 - 09.40 for 2 x 35 minutes with the teaching material